Application of Automatic Control System on Steam Boiler to Reduce Electric Power Consumption. Issue 1 (June 2019) - Syamsul; Mardiyanto, A; Zamzami; Amir, D; Suherman; Suprihardi
Abstract: This research focused on utilizing alternative energy sources in the nutmeg oil refining process. The purpose of this study is to obtain a more efficient energy source than fuel and gas energy sources in the steam boiler. The benefits of this research are reducing production costs, simplifying operations and reducing pollution in the distillation process. The method applied is to modify the steam boiler using an electrical energy source. Electric power consumption is based on the amount of temperature and pressure on the steam boiler. The desired temperature ranges from 100 ° C - 120 ° C, and the desired pressure is in the range of 1.0 - 2.0 bar. So that to maintain the temperature and pressure range is applied microcontroller-based electronic control. To improve the performance of the distillation system, the control works automatically. Testing on the steam boiler, by distilling as much as 20-25 kg of nutmeg in 16 hours. During this testing time, the electric power consumption decreased by 15%.